Stakeholder Analysis Waste Management in Tanjungpinang City - Hutahaean, Permata Pebester Natalia; Simangunsong, Damayanti; Mardiyanti, Elisa; Okta, Auliana; Lestari, Indah Puji (Center for Maritime Policy Governance Studies (CMPGS), 2024)
Solid waste management in urban areas has become a pressing environmental and governance issue, particularly in rapidly developing secondary cities such as Tanjungpinang, Indonesia. Despite the existence of regulatory frameworks like Regional Regulation No. 3 of 2015, the city's waste management system remains underdeveloped, marked by inefficient collection services, inadequate infrastructure, and limited public participation. This study aims to examine the stakeholder landscape in Tanjungpinang’s waste governance to identify institutional gaps, coordination challenges, and opportunities for improved collaboration. The research employs a qualitative and interpretive methodology, combining document analysis and stakeholder mapping using Eskerod & Jepsen’s influence-interest matrix and the Friedman and Miles stakeholder salience framework. Findings indicate that the Department of Environment (DLH) holds the highest level of authority but often lacks the urgency and resources needed for effective intervention. Meanwhile, actors with high urgency, such as informal waste workers and local communities, lack legitimacy and power, leading to their exclusion from formal governance processes. The stakeholder network is characterized by low mutuality and fragmented relationships, particularly between state and non-state actors. Waste banks and NGOs operate with limited support despite their significant roles in community outreach and recycling initiatives. The study concludes that sustainable urban waste management in Tanjungpinang requires inclusive governance reforms that build institutional capacity, strengthen stakeholder interdependence, and integrate informal actors into formal waste systems. These findings offer practical insights for enhancing stakeholder engagement and aligning local waste policies with Sustainable Development Goal 11 on sustainable cities and communities.